KARAKTERISTIK FISIK COOKIES PADA BERBAGAI RASIO TERIGU DENGAN TEPUNG UMBI DAHLIA DAN PENAMBAHAN MARGARIN [Physical Properties of Cookies Made from Different Ratio of Wheat with Dahlia Tuber Flours and Addition of Margarine] - Mubarok, Ahmad Zaki; Sembiring, Solisa Vania Joelita (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2020)
Cookies are one of the snacks, usually made from wheat flour and have high carbohydrate and fat but low fiber contents. In the present study, dahlia tuber flour was used to substitute wheat flour to produce fiber-rich cookies. The effect of dahlia tuber flour and wheat flour ratio and the addition of margarine were studied. The optimum formulation was obtained by Derringer’s desirability function, by comparing the closeness value of the physical properties of cookies made from dahlia tuber flour with control cookies made from wheat flour as a target. The result showed that optimum formulation to produce fiber-rich cookies obtained by using dahlia tuber flour and wheat flour ratio of 30:70 and margarine 75%, with total desirability (D) value of 0.84.